Cross-Border Nikah Sirri between Malaysia and Indonesia: Contemporary Legal and Social Dynamics in Borneo - Sri Wahyuni; Ahmad Abdlkareem Sarairah; Mohamed W. Abouyounes (MILRev: Metro Islamic Law Review, 2026)
This article examines the phenomenon of cross-border nikah sirri (unregistered marriage) between Malaysia and Indonesia in the Borneo region, particularly involving Malaysian Sarawakians and migrant labourers. The study aims to analyse the contemporary legal frameworks governing nikah sirri in both countries, explore the socio-cultural and structural factors that motivate cross-border marriage practices, and assess their implications for the protection of women’s and children’s rights. Employing a socio-legal approach, this research integrates primary data derived from in-depth interviews and field observations with secondary sources from relevant legal and academic literature. The findings reveal that undocumented migrant workers in Sarawak frequently cross into Indonesian border areas to conduct nikah sirri, facilitated by transnational kinship networks, including Dayak communities who provide social and ritual support. From a legal perspective, Malaysia strictly prohibits unregistered marriages and imposes administrative sanctions for them. In contrast, Indonesian law adopts a more accommodating stance by allowing post-facto legalisation through itsbat nikah (marriage confirmation) in the Religious Courts, alongside limited legal recognition for children. However, such cross-border practices are often treated in Malaysia as legal evasion and a violation of public order, rendering the marriages invalid and leaving women and children without formal legal protection, including issues related to lineage and civil status. From the perspective of maqāṣid al-sharīʿah, these practices tend to generate greater harm (maḍarat) than benefit (maṣlaḥah), particularly in failing to safeguard lineage (ḥifẓ al-nasl) and legal certainty. This study contributes to the discourse on transnational Islamic family law by offering a comparative and empirically grounded analysis of regulatory gaps and their social consequences. It further argues for an integrative approach to legal reform to strengthen cross-border protection mechanisms and ensure substantive justice for vulnerable groups.